Association of the RNF213 p.R4810K Variant With the Outer Diameter of Cervical Arteries in Patients With Ischemic Stroke - Eriko Yamaguchi; Takeshi Yoshimoto; Shiori Ogura; Kozue Saito; Satoshi Saito; Yorito Hattori; Kazuo Wasida; Kunihiro Nishimura; Kazunori Toyoda; Masatoshi Koga; Masafumi Ihara (Stroke: Vascular and Interventional Neurology, 2022)
Background We investigated the impact of the p.R4810K variant of RNF213 (ring finger protein 213) gene, a susceptibility gene of moyamoya disease in East Asia, on the outer diameter of cervical parts of carotid and vertebral arteries (VAs). Methods We examined consecutive Japanese patients with ischemic stroke who underwent carotid ultrasonography between 2015 and 2019. Patient background and the carotid ultrasonography‐measured outer diameter of extracranial cervical arteries, including the common carotid artery, internal carotid artery, external carotid artery, and cervical VA, were compared between variant carriers and noncarriers. Outer diameters of each artery were defined as the mean distance from far to near wall adventitia of right and left target arteries using carotid ultrasonography. The average diameter of both cervical portions of common carotid arteries, internal carotid arteries, external carotid arteries, and the dominant side diameter of both cervical VAs were used. Results Of the 617 adult patients (204 women; median age, 74 years) analyzed, 26 (4.2%) carried the RNF213 p.R4810K variant. Variant carriers were significantly younger (P<0.01) and had more frequent steno‐occlusion of the M1 segment of the middle cerebral artery (P<0.01). Multivariate logistic regression analysis showed that variant carriers had significantly smaller mean diameters in the common carotid artery (7.25 versus 8.22 mm; adjusted odds ratio [aOR] per 1 mm decrease, 2.94; 95% CI, 1.69–5.00), cervical internal carotid artery (4.99 versus 5.55 mm; aOR, 1.66; 95% CI, 1.03–2.70), and cervical VA (3.55 versus 4.10 mm; aOR, 2.56; 95% CI, 1.33–4.76) than noncarriers. Mean diameters of the common carotid artery (aOR, 3.44; 95% CI, 2.08–5.88) and cervical internal carotid artery (aOR, 2.04; 95% CI, 1.23–3.33) and the dominant diameter of the cervical VA (aOR, 3.23; 95% CI, 1.72–5.88) were also smaller in variant carriers even when the analysis was restricted to patients without bilateral steno‐occlusion in target vessels or intracranial arteries distal to target vessels. Conclusion RNF213 p.R4810K variant carriers have smaller cervical arterial outer diameters in both anterior and posterior circulations than noncarriers with ischemic stroke. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT02251665.